Immigration and C-sections incidence: Maternal care and perinatal outcomes in the context of the pandemic in Chile - Carroza Escobar, María Begoña; Silva, Nicole; Ortíz-Contreras, Jovita; Villegas, Rodrigo; Vargas, Sergio L.; Núñez, Claudio; Vergara Maldonado, Luis Felipe; Villanueva, Loreto Paola (Frontiers in Global Women's Health, 2023)
Introduction Immigration has increased significantly in Chile. Despite that all pregnant women, regardless of nationality and immigration status, have the right to access to all healthcare services during pregnancy, childbirth, and postpartum, inequities in health care outcomes and health provision have been reported. During COVID-19 pandemic, these inequities are completely unknown. Objective The aim of this study was to compare the incidence of c-sections according to mother's migration status, as well as other maternal care and perinatal outcomes in women giving birth at San José Hospital in Santiago, Chile, during the COVID-19 pandemic. Methods A retrospective cohort study was designed including 10,166 registered single births at the San José Hospital between March 2020 and August 2021. To compare between groups, statistical tests such as Chi-square and Fisher's exact were used. Log Binomial regression models were performed adjusted for potential confounding variables. To estimate the strength of association the relative risk was used. Results Immigrant mothers account for 48.1% of the registered births. Compared to non-immigrant women, immigrants exhibit a higher proportion of c-section, specifically, emergency c-section (28.64% vs. 21.10%; p-value < 0.001) but a lower proportion of and having a preterm birth (8.24% vs. 13.45%; p < 0.05), receiving personalized childbirth care (13.02% vs. 14.60%; p-value < 0.05), companion during labor and childbirth (77.1% vs. 86.95%; p-value < 0.001), And postpartum attachment to newborn (73% vs. 79.50%; p-value < 0.001). The proportion of COVID exposure was not significant between groups, not the severity also. Haitians had a highest risk of undergoing emergency c-section (aRR = 1.61) and Venezuelans had a highest risk of elective c-section (aRR = 2.18) compared to non-immigrants. Conclusion This study reports high rates of c-sections in the entire population, but in immigrant populations it is even higher. Additionally, it found gaps in maternal care and perinatal outcomes between immigrants and non-immigrants. More studies are needed to elucidate the possible causes of these differences and establish new regulations to protect the reproductive rights of the immigrant population.